Hideaway - Brett, Leonard; Molina, Alfred; Alicia Silverstone; Christine Lahti; Jeremy Sisto; Kenneth Welshv; Rae Dawn Chong; Jeff Goldblum (USA TriStar Pictures, 1995)
Hatch Harrison had a traffic accident with his car. At first the doctors said he was dead but then they succeeded to bring him back to life after two hours. But Hatch starts to have strange sensations in following time and discovers that he is now united with a mad killer who had entered his mind during his death.
Hatch Harrison had a traffic accident with his car. At first the doctors said he was dead but then they...
Dean R. Koontz
Languages: English, French, Spanish, German
Subtitles: English, French, German, Italian, Spanish, Dutch, Arabic, Czech, Dannish, Finnish, Greek, Hebrew, Hindi, Hungarian, Icelandic, Norwegian, Polish, Portuguese, Swedish, Turkish
Keywords: Thriller; Fantasy